Validation of developed method by RP-HPLC for simultaneous estimation of famotidine and ibuprofen in human plasma and studying the stability of the drugs in plasma - Ashutosh, K. S; Manidipa, D.; Seshagiri, R. J. V. L. N.; Gowri, S. D. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The RP-HPLC separation was carried out by reverse phase chromatography on a Symmetry C18 (4.6 x 150 mm, 3.5 μm, make: XTerra) with a mobile phase composed of sodium dihydrogen ortho phosphate [pH 2.5] and acetonitrile in the ratio of 30:70 v/v in an isocratic mode at a flow rate of 1.2 mL/min. The run time was maintained for 8.0 min. The detection was monitored at 236 nm. The accuracy was calculated in human plasma and the % recovery was found 99.80 - 99.85 for famotidine and 99.56 -99.85.5 for ibuprofen and reproducibility was found to be satisfactory. The calibration curve for famotidine in human plasma was linear over 3.32 to 6.65 μg/mL and 100- 200 μg/mL for ibuprofen in human plasma respectively. The inter-day and intra-day precision in human plasma was found within limits. The proposed method has adequate sensitivity, reproducibility, and specificity for the determination of famotidine and ibuprofen in plasma. The LLOQ obtained by the proposed method in human plasma were 1.24 and 5.0 μg/mL for famotidine and ibuprofen respectively. The proposed method is simple, fast, accurate, and precise for the quantification of famotidine and ibuprofen in plasma as per the ICH guidelines. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016, Page: 34-48